PERSPEKTIF AGILE UNTUK PENGEMBANGAN SUMBER DAYA MANUSIA - Panca Tuah Tuha; Roy Haris Oktabian (LPPM STIE PERTIBA Pangkalpinang, 2022)
Many companies are undergoing management reforms. The emergence of the term Agile in this transformation has become an option. A basic understanding of agility in the concept of agile HR as an operational strategy for the HR function is critical to understanding it comprehensively. A concept emphasized in this perspective is the focus on people agility. To understand the emergence of Agile HR as an HR operational strategy, this study is a historical schema that tracks corresponding changes in organizational strategy, talent management, and HR operating models over time. The interaction between strategy and HR strategy makes it possible to understand how HR agility as an operational strategy has emerged as a means to address the challenges presented by the new wave of strategy/HR/management models and explore where agility as an operational HR strategy can take place.